The Relationship between Exchange Rate and Stock Market Performance: Empirical Evidence from Sri Lanka - Anusha, P.; Dhushanthan, B.; Vinayagathasan, T. (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The stock market is one of the fastest-growing sectors in the world at present. Such a stock market can be seen growing in Sri Lanka as well. The performance of a stock market is affected by various factors. Among those factors, foreign market stock prices, GDP, corporate performance, and the exchange rate are important. Of these, the exchange rate is the crucial one. Data of exchange rate depict the increasing pattern over time while stock market performance shows high fluctuation in Sri Lanka. Thus, this research aims to identify the impact of the exchange rate on the performance of the Colombo Stock Exchange (CSE). For this purpose, we used price index of all stocks, exchange rate, inflation, foreign direct investment, and interest rate as the variables. We employed annual secondary data from Central Bank of Sri Lanka over the period of 1985 – 2018. The Augmented Dickey Fuller and Phillips Perron unit root tests approaches confirmed that none of the variables are I(2) which allows us to examine the long-run relationship between the variables using Auto-Regressive Distributed Lag (ARDL) bounds testing method. AIC is suggested to employ ARDL(1,1,0,4,4) model among the top 20 models. The bounds testing results detected the cointegrating relationship between the variables. Our results also suggest that there is no correlation between exchange rate and all share price indexes in the long run, whereas there is a positive relationship between exchange rate and all share price indexes in the short run. Inflation has a positive impact on all share price indexes in the long run while it does not have significant impact on all share price indexes in the short run. Moreover, the interest rate has a negative and weakly significant impact on all share price indexes both in the long run and in the short run. The Granger causality test indicates that there is a unidirectional causality between the price index of all stocks and the exchange rate. Therefore the results of this research emphasize that the exchange rate can be used as a policy tool to increase stock market performance.